(untitled) (Romano-arabica, 2025)
This research presents an innovative methodology for teaching and studying classical Arabic poetry, with particular emphasis on its humorous elements. The study centers on analyzing the works of the Abbasid poet Abu al-Shamaqmaq, employing contemporary theories of humor in the examination of his poetic output. This approach, developed as part of my doctoral thesis,2 integrates theoretical frameworks derived from psychology, philosophy, and sociology with the practical analysis of classical Arabic poems. The methodology offers a novel interdisciplinary perspective on understanding and interpreting medieval Arabic literary humor. This article is divided into two sections. The theoretical section provides a brief overview of selected theories of humor. The practical section applies these chosen theories to the poem, demonstrating how these theories manifest within it.